(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The organizational culture of foundations task the and the organization difference their work , the more sought management organization to strengthen the working has increased loyalty organizational thus was reflected this on the success of the organization. This study was conducted to investigate the effect of the study variable on the study site (medical syringes company in Babylon governorate) organizational objectives. The problem of the study was the absence a clear perception of the study sample on the effect of organizational affiliation. The most important suggestion and conclusions were the need for the study organization to consider the variable of the study with more attention and to learn through the training courses on this